Depression and infertility: evaluation of 681 infertile women using Beck depression inventory - Khademi A; Alleyassin A; Agha-hosseini M; Ahmadi Abhari A; Esfhandi H; Fakhimi Derakhshan K (Tehran University of Medical Sciences, 2004)
Introduction: Infertility and depression are major problems of today's societies. Although depression is one of the most prevalent diseases in primary care practice, consult for receiving help is carried out much less than true prevalence of the disease. Therefore gathering information about prevalence and risk factors of depression is very valuable. Beck Depression Inventory (BDI) which is a screening tool for depression can be used in Iranian patients because of availability of a validated translation. The objective of this study was to estimate the prevalence of depression in infertile subjects in an infertility center. Materials and Methods: In this study, 681 infertile women were evaluated in Shariati Hospital, Tehran. Demographic information's including age, duration, type and cause of infertility, level of education, previous treatments and smoking habits were recorded. BDI was completed by patients and score was estimated. Score of 16 and higher was assumed positive. Results: There was no relationship between age and prevalence of positive BDI score, but prevalence of positive BDI score was higher in infertilities of longer duration, infertilities caused by both male and female factors and in patients with low level of education and history of previous treatment or surgical therapy. Conclusion: Infertile patients are at risk of depression. Rate of consulting with psychiatrists and getting help is low in our country due to cultural aspects, so screening of high risk subgroups in infertile patients and referring them to psychiatrist would be very helpful.